(untitled) (Cultura Económica, 2018)
Miguel Alfonso Martínez-Echevarría is one of the last representatives of Spanish economic humanism. This essay will try to show what kind of operation it may be to infuse Economy with something like a humanist spirit, not meaning by this a violation of its autonomy or scientific quality, or doing something that resembles pure rhetoric. In this attempt, the author goes back to the history of economic humanism in its Spanish version. Finally, it will seek to reveal how current experience confirms an idea that many had considered obsolete, but that Miguel Alfonso has always maintained: that the path of humanistic detour ends up being more efficient for the economy than all the supposedly scientific shortcuts that seek to avoid it.